The Implementation of Presentation, Practice, and Production (PPP) in enhancing Students’ Writing Ability - Ni Putu Riska Dewi; Ni Wayan Krismayani; Dewa Ayu Ari Wiryadi Joni (International Journal of Applied Science and Sustainable Development (IJASSD), 2023)
One of the four essential skills that must be learned is writing ability. The majority of junior high school students struggled with their writing abilities. The purpose of the current study was to ascertain if classroom action research may increase PPP among seventh-grade students at SMP Negeri 12 Denpasar during the academic year 2022–2023. The pre-test, post-test, and questionnaire were the researcher's instruments for achieving the goal of the current study. Pre-test results from the pre-cycle indicated that the subject's writing abilities were good, mainly descriptive paragraphs. The current classroom action research was subsequently completed using PPP. The second session's post-test I result revealed that the subject had made less progress than the previous pre-test. The results of the post-test II from the previous session also demonstrated significant improvement in the subject's writing abilities, which went from a decent level to an excellent one. Additionally, this study demonstrated that learning behaviour had changed because of the technique's success in enhancing the subject's writing abilities. In conclusion, the current classroom action research demonstrated that PPP might enhance the writing abilities of seventh-grade students at SMP Negeri 12 Denpasar in the academic year 2022–2023. The subjects also gave positive responses. Keywords: Implementation, Writing, PPP